Denoise-and-forward based adaptive diversity scheme for physical-layer network coding with multiple relay node - Rui-feng GAO; Xiao-dong JI; Zhi-hua BAO; Shi-bing ZHANG; Chen XU (Tongxin xuebao)
The capacity issue of a denoise-and-forward(DNF) protocol was focused on based PNC system of frequency non-selective Rayleigh fading channel.First,the total sum-rate of the system was derived.With the derived sum-rate expression,two policies maximizing the system sum-rate are proposed.On this basis,a novel adaptive diversity scheme was proposed.Closed-form expressions of the system outage probability with the new proposed scheme as well as the amplify-and-forward (AF) based PNC system and the conventional direct transmission were derived over frequency-nonselective Rayleigh fading channels.Simulation experiments are conducted and the results show that the outage performance of the system can be im-proved significantly compared to the AF based PNC system and the conventional direct transmission scheme.